Case Report: Congenital hepatic hemangioma with arteriovenous fistula: 2-year multidisciplinary management and outcomes - Renping Mao; Weiwei Ruan; Jianming Zhu; Li Li; Haiyan Jiang; Yanhong Li (Frontiers in Pediatrics)
BackgroundCongenital hepatic hemangioma with arteriovenous fistula (HHAVF) is a rare condition in newborns that may manifest as respiratory distress, pulmonary hypertension, and heart failure shortly after birth. This report describes a case of HHAVF complicated by encephalomalacia identified after transcatheter arterial embolization (TAE). However, the condition improved with multidisciplinary management and long-term follow-up.Case presentationA full-term female infant presented with a cardiac murmur and pulmonary hypertension at birth. Contrast-enhanced CT demonstrated multiple hepatic hemangiomas with high-flow arteriovenous shunting. Pulmonary hypertension resolved after TAE; however, the recurrence of hepatic hemangioma required oral propranolol therapy, which led to complete regression by 18 months of age. Postprocedural imaging identified encephalomalacia in the right frontotemporal and parietal lobes, as well as the basal ganglia, concurrent with left-limb motor impairment. Long-term rehabilitation improved left-limb function and the extent of encephalomalacia stabilized.ConclusionsCurrent research primarily focuses on early cardiopulmonary complications in HHAVF, while multidisciplinary management strategies and long-term outcomes, particularly neurological manifestations, are rarely reported.